Micropropagation and alkaloid production in Stemona sp. - K. Chotikadachanarong (2018)
Stemona sp. has been used an antifungal, anti-parasitic, demulcent, and insecticidal herb. The objectives of the study were to select suitable explant and medium for micropropagation of Stemona sp. and to compare secondary metabolites found in natural tissue with those found in cultured tissue. The explants from terminal and axillary bud and bud adjacent to tuberous root were cultured on MS medium supplemented with 0, 1, 2 and 3 mg/L BA for 4 weeks and all transferred to 2 mg/L BA for another 8 weeks. The best growth was obtained from MS medium supplemented with 3 mg/L BA and followed by 2 mg/L BA which could induce the explants of bud adjacent to tuberous root to produce 71.25% callus and 70.09% multiple shoots. The calli were then cultured in liquid and on semi-solid MS medium supplemented with 0, 1, 2 and 3 mg/L NAA for 1 month to increase root formation. Semi-solid MS medium supplemented with 2 and 3 mg/L NAA stimulated 100% root induction from calli with an average of 12 and 14 roots/explant respectively. Different compounds from crude extracts of shoot, callus and root of Stemona sp. in dichloromethane were separated by thin layer chromatography. A mixture of toluene:ethyl acetate (80:20 v/v) was used as mobile phase and the separated substances were detected by UV light. The result indicated that natural root, callus and root from tissue culture had the same bands at Rf0.02, 0.06, 0.14, 0.19, 0.42, 0.56, 0.69 and 0.85 and showed the semilar positive alkaloid bands at Rf0.02. © ISHS 2005.